Implementing Minister of Social Affairs Regulation No. 9 of 2025 on Karang Taruna: A Siyasah Tanfidziyyah Perspective on Youth Development in Indonesia - Siti Mariyam; Linda Firdawaty; M. Yasin Al Arif (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
Karang Taruna plays a strategic role as a community-based youth organization in promoting youth development and social welfare at the village and urban-village levels in Indonesia. Minister of Social Affairs Regulation No. 9 of 2025, which amends Minister of Social Affairs Regulation No. 25 of 2019 on Karang Taruna, provides a renewed legal basis for strengthening institutional responsibility and expanding youth participation. This study analyzes the implementation of Article 43A, which concerns the responsibilities of Karang Taruna administrators, and Article 18 paragraph (1), which regulates the passive membership system, in Gedong Meneng Baru Urban Village, Bandar Lampung. It also examines the extent to which such implementation reflects the principles of siyasah tanfidziyyah. This study employs empirical legal research using a qualitative socio-legal approach. Data were collected through semi-structured interviews and documentation study, and were analyzed through the principles of al-tanfīdh and al-bayān. The findings show that the implementation of the regulation remains suboptimal due to limited funding, organizational inactivity, weak administrative capacity, low youth participation, limited institutional communication, and weak leadership regeneration. From the perspective of siyasah tanfidziyyah, strengthening Karang Taruna requires institutional revitalization, capacity building for administrators, systematic youth data collection, budgetary support, and participatory communication to transform formal membership into substantive youth engagement